THER-23. RESULTS OF THE ZERO CHILDHOOD CANCER INTEGRATED PRECISION MEDICINE PLATFORM FOR PAEDIATRIC HIGH-RISK BRAIN TUMOURS. (23rd April 2019) - Tsoli, Maria; Lau, Loretta; Barahona, Paulette; Mayoh, Chelsea; Failes, Tim; Wong, Marie; Sherstyuk, Alexandra; Gifford, Andrew J; Kumar, Amit; Mould, Emily; Ung, Caitlin; Tolhurst, Ornella; et al.
Abstract: Brain tumours represent the most common solid tumour of childhood and result in significant morbidity and mortality. The Zero Childhood Cancer national child precision medicine program aims to identify targeted therapeutic agents for high-risk paediatric malignancies (expected survival <30%) including brain tumours. Here we will report on the Pilot Feasibility Study (TARGET) and the initial experience of the National Clinical Trial (PRISM), which opened in September of 2017. A total of 200 patients have been enrolled, 59 in the pilot phase (TARGET) and 141 in the National study (PRISM) out of which 77 patients (38.5%) had CNS malignancies, of which 64 cases have completed curation. Molecular analysis of these cases identified actionable molecular aberrations in 47 patients (73.4%). Ten cases (15.6%) had a reportable germline cancer predisposition variant. Overall, the most common aberrant genetic changes observed include TP53 mutations, CDKN2A/B biallelic loss, PDGFRA over-expression mainly in the presence of amplification, and fusions containing either NTRK or BRAF. In 2 cases, the somatic genomic findings changed the primary diagnosis. Fresh tissue collection permitted in vitro high throughput screening (HTS) (120 single agents) in 32/69 (46.3%) of cases with additional cultures currently under development. Hits were identified in 2 cultures and recommendations were made. Four PDX models from successful primary cultures were established where single and combination drug efficacy studies have been performed based on recommendations made from molecular profiling or HTS analysis. Currently multiple PDX models are under evaluation either from successful primary cultures or direct intracranial injection of biopsies. In this study we will present an overview of the molecular and preclinical platforms and their impact on the management of paediatric patients with aggressive brain tumours.